Slow motion iterations of all my whereabouts ever - Konopka, Cole, author; Steensen, Sasha, advisor; Beachy-Quick, Dan, committee member; Jones, Laura, committee member (Colorado State University. Libraries, 2018)
Slow motion iterations of all my whereabouts ever charts the development of an unnamed speaker as they explore different relationships with the self, often represented by the first-person pronoun, the I. The manuscript progresses from a confusion over the self through a resistance to it, followed by an abundance of self, a lapse of the self, and finally a plurality of self. These transitions take place in form, as well as in the context of the poems themselves, which contemplate the macabre in life.
Keywords: poetry